Sobre los planes de intervención de José I en Madrid - Lopezosa Aparicio, Concepción (Cuadernos de Historia Moderna, 2011)
This paper examines Madrid urban policy undertaken and followed by Joseph Bonaparte during his brief and complex reign in Spain. It considers different aspects of his urban planning, such as the project assessment, but it studies also the continuity factor of the city planning before 1808 and the impact of these new public works in the urban development of Madrid since 1814.